The Politics of Iraq’s Waterscape: 1920-2024 - John, Meg (Blue Papers, 2026)
Iraq and the Kurdistan Region of Iraq (KRI), historically a landscape with abundant water resources, has undergone significant geopolitical changes over the last century. Today, the country must find solutions for extreme water shortages. Dukan Dam serves as an example of how hegemonic and hierarchical effects from recent history have influenced water governance. While population growth and climate change along with unilateral water resource activities undertaken by neighboring states are exacerbating water shortages for Iraq and the KRI, it is important to analyze the internal waterscape and how it is managed. In this article, I focus on the period from 1920 to 2024 in Iraq to shed light on problems of governance strains pertaining to water. To achieve Sustainable Development Goal 6: Clean Water and Sanitation, Iraq must reckon with its past to ensure a sustainable future for generations to come.
Keywords: inclusive society; water; governance; Dukan Dam; sustainable development